A Smart Nanoprobe for Visually Investigating the Activation Effect of Cyclical DOX Release on the p53 Pathway and Pathway-Related Molecules - Ping Sun; Chunlei Gao; Zhe Chen; Siyu Wang; Gang Li; Mingming Luan; Yaoguang Wang (Biosensors)
Developing appropriate methods for real-time in situ investigation of how drugs influence signaling pathways and related biomolecules holds enormous potential for helping to provide an understanding of how anticancer drugs exert their effects. Herein, we report a smart nanoprobe, PDA-MB (DOX)-Pep, constructed on the basis of polydopamine nanoparticles (PDA NPs) modified with a dense shell of molecular beacon (MB) with embedded doxorubicin (DOX) and peptide, which can respond specifically to miRNA-34a and Caspase-3 targets. Intracellular experiments demonstrated that, in comparison to the control nanoprobe PDA-MB-Pep, the smart nanoprobe could selectively respond to miRNA-34a, facilitating the release of the embedded DOX. The released DOX subsequently activated the p53 pathway, which further upregulated miRNA-34a expression, leading to additional DOX release. This initiated a cyclical process involving the probe’s response to miRNA-34a, DOX release, p53 activation, and miRNA-34a upregulation, ultimately enhancing cell apoptosis and increasing Caspase-3 expression. The designed smart nanoprobe offers a visual approach to explore how anticancer drugs influence signaling pathways and related molecules at the cellular level.